2020
DOI: 10.31234/osf.io/jmctv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress, functioning, and coping during the COVID-19 pandemic: Results from an online convenience sample

Abstract: This study explored how individuals living in the United States were experiencing and responding to stress related to the COVID-19 pandemic in May 2020. Participants (N = 408; 60% non-Hispanic White) completed an online survey regarding traumatic stress, functional impairment, and use of and perceived helpfulness of various coping strategies. Results showed that 37% of participants endorsed clinically-elevated PTSD symptoms. Approximately half of participants reported changes in their daily functioning from be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 8 publications
4
29
1
Order By: Relevance
“…We recruited online participants from five English speaking western countries of similar socio-economic make up (United States, United Kingdom, Canada, Australia and New Zealand). To date, research on COVID-19 as a traumatic stressor has primarily been conducted in China [ 3 ], and only one unpublished study has focused on one of our populations of interest (United States [ 26 ]). Furthermore, published research to date has focused on providing a snapshot of mental health related concerns (e.g., rates of PTSD, depression etc.…”
Section: Introductionmentioning
confidence: 99%
“…We recruited online participants from five English speaking western countries of similar socio-economic make up (United States, United Kingdom, Canada, Australia and New Zealand). To date, research on COVID-19 as a traumatic stressor has primarily been conducted in China [ 3 ], and only one unpublished study has focused on one of our populations of interest (United States [ 26 ]). Furthermore, published research to date has focused on providing a snapshot of mental health related concerns (e.g., rates of PTSD, depression etc.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies from China on the psychological impact of COVID‐19 reported 35%–53.8% of adults experienced moderate or severe psychological symptoms (Qiu et al, 2020; Wang et al, 2020). In the United States, studies in adults conducted for 2–10 days during this pandemic showed increased loneliness, worries and stress, clinically significant depression and PTSD symptoms, and suicidal ideation (Ammerman et al, 2020; Killgore et al, 2020; Panchal et al, 2020; Park et al, 2020; Rosenberg et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as health concerns, such as oneself or a loved-one contracting the virus; financial stress related to loss of income or the pandemic-induced economic downturn; disruptions to daily life, childcare, and education due to lockdown restrictions; and general uncertainty about the future and feelings of helplessness contribute to reports of increased stress [ 3 , 4 ]. However, while a majority of the global population has experienced pandemic-associated environmental stressors, there is substantial individual variation in the quantity and severity of stressors experienced, and in behavioral and physiological responses to those stressors [ 5 , 6 ]. Psychological characteristics such as cognitive flexibility may help reduce stress response [ 7 ].…”
Section: Introductionmentioning
confidence: 99%